The Influence of Service Quality Dimensions on Customer Loyalty in PT JNE North Bandung Area - Abdul Quddus, Fakhri Syahir; Hudrasyah, Herry (Journal of Business and Management, 2014)
This study examines how each dimension of service quality may exhibit different impacts on customer satisfaction and customer loyalty in the service delivery context. PT. JNE is one of the many players in service delivery field. The business is capable to facilitate industrial producers and consumers to transact, to minimize the time, as well as acquiring new business opportunities from the needs of customers who have not been reached. Customer is the key to winning the competition among other business practitioners. Service quality is an important element in the marketing mix that affects the customer. Service quality is a major factor that affects a customer in terms of increasing customer loyalty. The main purpose of this study is to examine how each dimension of service quality may influence customer satisfaction and customer loyalty among PT. JNE customers. This final project is limited in the scope of data. The data which are analyzed were gained in North Bandung, Indonesia. The respondents also limited to people that already experiencing the service at PT. JNE North Bandung area. The distribution of questionnaire of this research will be conducted in PT. JNE branches around North Bandung area. A survey research with judgment sampling was conducted with 178 JNE customers. Descriptive analysis, Frequency analysis, Regression analysis, Correlations analysis, and Path analysis were used to evaluate the data and make data analysis.The results reveal that service quality dimensions significantly influences customer satisfaction; customer satisfaction significantly influences customer loyalty; and also reveal that service quality dimensions do significantly influence the Customer Loyalty through Customer Satisfaction. Research implications and future research directions conclude the study report. Keywords: service quality, customer satisfaction, customer loyalty, PT. JNE